Correlation among Structure, Microstructure, and Electrochemical Properties of NiAl–CO3 Layered Double Hydroxide Thin Films - Faour, A; Mousty, C; Prevot, V; Devouard, B; De Roy, A; Bordet, P; Elkaim, E; Taviot-Gueho, C (Journal of physical chemistry. C, 2012)
We studied a series of NiAl–CO3 layered double hydroxides (LDHs) of various degrees of crystallinity prepared by a glycine-assisted hydrothermal method. The structures and the microstructures were determined by Rietveld refinement with a spherical harmonic-implemented algorithm using high-resolution synchrotron powder X-ray diffraction (XRD) data. These XRD results combined with transmission electron microscopy (TEM) observations indicate that the broadening of 00l diffraction lines is mainly due to size effects, while both size and strain effects contribute to the anisotropic broadening of the other hkl reflections. The in-plane TEM dimensions of LDH platelets are found larger than the coherent lengths in the 110 direction, indicating a noncoherent coalescence of domains during crystal growth. The DIFFaX program was also used to model structural defects, i.e., CO3 2–/SO4 2– interstratification and intergrowth between rhombohedral 3R1 and hexagonal 2H1 polytypes. Furthermore, the distribution of the cations within the hydroxide layers has been determined by the atomic pair distribution function technique, indicating a disordered distribution of the cation in all samples with absolutely identical cationic coordination spheres. The electrochemical characterization of these samples as thin-film modified electrodes, by means of cyclic voltammetry and electrochemical impedance spectroscopy measurements, reveals complex behaviors which are the result of competing effects between the coherent domain size and the particle size, the aggregation state of LDH particles, the Ni bulk concentration, and the presence of structural defects. Remarkably, the presence of the 2H1 stacking motifs in the 3R1 LDH matrix results in an increased electrochemical signal. Either the location of metal cations exactly on top of the others in the 2H1 polytype or the defects associated with the intergrowth of 2H1–3R1 polytypes may be responsible for the enhanced electroactivity of Ni centers.